2013
DOI: 10.1080/21615667.2013.10878973
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Some Physical Fitness and Anthropometric Measures Between Greco-Roman and Freestyle Wrestlers

Abstract: The purpose of this study was to investigate the differences in physical fitness and anthropometric measures between Greco-Roman and freestyle wrestlers. Thirty three Iranian elite wrestlers (Freestyle, age: 24.54±3.43 years, N=13) and (Greco-Roman, age: 23.05±1.95 years, N=20) who were invited to the training camps participated in this study. The anthropometric traits included height, sitting height, arm-span, and the physical fitness traits included flexibility (sit-and-reach test), muscular endurance (pull-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
1
9
1
Order By: Relevance
“…The main difference is that Greco-Roman wrestlers are forbidden from performing any holds below the waist, whereas in freestyle they are allowed to use their whole body during the fight [2]. A great body of studies dealing with differences in physical, physiological or psychological profiles between wrestling styles revealed that there are no significant differences between Greco-Roman and freestyle wrestling [3][4][5]. A few studies, however, have found some differences between both wrestling styles.…”
Section: Introductionmentioning
confidence: 99%
“…The main difference is that Greco-Roman wrestlers are forbidden from performing any holds below the waist, whereas in freestyle they are allowed to use their whole body during the fight [2]. A great body of studies dealing with differences in physical, physiological or psychological profiles between wrestling styles revealed that there are no significant differences between Greco-Roman and freestyle wrestling [3][4][5]. A few studies, however, have found some differences between both wrestling styles.…”
Section: Introductionmentioning
confidence: 99%
“…Most investigations regarding wrestlers' RT have focused on performance (match result) of competitors Kroll, 1958;Mirzael et al, 2011), weight class (Rashid, Nejad, Khodayari, & Mohammadi, 2012;Singer & Weiss, 1968), the type of match (Gierczuk, 2008;Mirzael, Curby, Barbas, & Lofti, 2013), and physiological factors (Cankaya, 2012). MT, which is the other component of quick reaction, has not been analyzed as thoroughly, despite its correlation with performance being stronger than the correlation of RT with performance (Whitley & Montano, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…All else being equal, longer arms enable a person to strike an opponent, with fist or weapon, while being out of range of retaliation. It also makes grabbing an opponent easier, which may aid in grappling (discussed in Mirzaei, Curby, Barbas, & Lotfi, 2011, 2013), and keeping opponents at a greater distance can allow for better defense. Further, it produces greater momentum for weapon swings and punches thrown with a wide arc (known as “haymakers” in combat sports), because the further distance from the shoulder joint allows the person to increase velocity (though punching power also heavily involves bodily rotation and force generation of the legs, see Lenetsky, Harris, & Brughelli, 2013).…”
mentioning
confidence: 99%